Takdir Islam dalam Perspektif Dakwah: Kajian Faktual Fenomena Generasi Muda Serba Instan di Kabupaten Sleman Yogyakarta - Yusuf, Mochamad Aris; Mujahidah, Fikriyatul Islami; Mujiyati, Mujiyati (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2023)
This article will respond to how the concept of destiny makes this instant youth enthusiasm to involve Allah SWT in every behavior and determination of a search and secret that should not be disappointed. This study is based on factual phenomena that occur among the younger generation in Sleman Regency, Yogyakarta. This factual study was analyzed using a da'wah perspective. This research method uses a qualitative descriptive with an exploratory study, the primary data in this article is the young generation who think instantly. The results of the study show that the factors behind suicide in the younger generation are the main triggers for depression, extreme thoughts on interpreting the world, so young people who think instantly are advised to respond to life by knowing levels or destiny as the main foundation as stipulated by Allah SWT, namely by having faith, but not all the deeds he does are destiny. Because the basis of destiny is not absolute provision of Allah SWT, there is a law of causality, namely causation. However, Allah swt gives help to every servant of His who asks for help. If the younger generation finds it difficult, then pray.